Duck hunting bag estimates for the 2013/14 season in France - Guillemain, Matthieu; Aubry, P.; Folliott, B.; Caizergues, A. (Wildfowl, 2016)
A national survey of duck bags was carried out during the 2013/14 hunting season in France, for the first time in 15 years. An estimated total of over 2 million dabbling and diving ducks were shot in the country, half of which were Mallard Anas platyrhynchos. Proper statistical comparisons with earlier French surveys or with similar data from other countries were not possible because of the different (and sometimes unknown) sampling protocols, but the general trends suggest a relatively stable hunting bag compared to 15 years ago. France remains the European country reporting the greatest number of ducks harvested annually as a result of a long tradition of wildfowling, a dense human population and a central geographic position within the duck flyways. The only major change was a massive decline in the estimated harvest of Common Pochard Aythya ferina, reflecting a similar pattern in other countries and the poor conservation status of the species in Western Europe. Waterfowl hunting bag survey methods should be harmonised in the future, if coordinated adaptive management of populations is to be set in place at the flyway scale.